ANALISIS RASIO LIKUIDITAS, PROFITABILITAS, SOLVABILITAS DAN AKTIFITAS SEBAGAI ALAT PENILAIAN SERTA IMPLEMENTASINYA TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PT. ANEKA TAMBANG TBK - Arief Muda Kusuma; Wening Estiningsih (LPPM Institut Pendidikan Nusantara Global, 2023)
A company's financial performance is assessed using financial ratio analysis. PT. Aneka Tambang Tbk is a company that operates in the mining sector with a fairly wide market. The purpose of this study is to analyze the financial performance of PT. Aneka Tambang Tbk by using liquidity, profitability, solvency, and activity ratios as assessment tools. The data used in this research are the financial statements of PT. Aneka Tambang Tbk for the period 2017-2019 which were obtained from the official website of the Indonesia Stock Exchange. The analysis of ratios is conducted using the ratios of liquidity, profitability, solvency, and activity. The research results show that the financial performance of PT. Aneka Tambang Tbk in the period 2017-2019 showed an increase in the liquidity ratio, profitability, solvency, and activity. This increase shows that the company is able to manage assets well, increase operational efficiency, and have the ability to meet its financial obligations. The study found that PT. Aneka Tambang Tbk has good and healthy financial performance. The implications of these findings are that the company can continue to improve its financial performance by optimizing asset management and maintaining its financial obligations. This study can also serve as a reference for those interested in knowing the financial performance of a company in the mining sector.